2020
DOI: 10.1177/1120672120908719
|View full text |Cite
|
Sign up to set email alerts
|

En-face choroidal vascularity in central serous chorioretinopathy

Abstract: Purpose: To evaluate the choroidal vascularity index of eyes for acute and chronic central serous chorioretinopathy patients using swept-source optical coherence tomography generated en-face scans. Methods: This was a retrospective study, in which slabs of en-face optical coherence tomography scans, at 5 μm intervals, spanning from the retina to choroid, were binarized using a validated algorithm to calculate choroidal vascularity index. The choroidal vascularity index was defined as the ratio between the chor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
2
11
1
Order By: Relevance
“…This shows similar trends in CVI increasing towards maximum at the mid choroid and similar values at different depths of the choroid in both acute and chronic CSCR. Choroidal status looks similar in both acute and chronic disease [ 66 ].…”
Section: Results/findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows similar trends in CVI increasing towards maximum at the mid choroid and similar values at different depths of the choroid in both acute and chronic CSCR. Choroidal status looks similar in both acute and chronic disease [ 66 ].…”
Section: Results/findingsmentioning
confidence: 99%
“…As described earlier, there is dilatation of Haller’s layer, which is the layer of outer large choroidal vessels, and attenuation of Sattler’s layer and the choriocapillaris in a diseased state. In a retrospective study of 30 eyes, Wong et al showed the mean CVI of eyes with acute disease was 45.21% ± 2.25% at the choriocapillaris, which increased to the maximal value of 48.35% ± 2.06% at 75% depth of the choroidal thickness and 45.31% ± 3.27% at the choroidoscleral interface [ 66 ]. In eyes with chronic disease, the mean CVI was 44.76% ± 2.60% at the choriocapillaris, which hit a maximum at 50% choroidal depth (48.70% ± 1.32%) and then returned to 45.41% ± 6.02% at the choroidoscleral interface.…”
Section: Results/findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have confirmed the peculiar morphology of the choroidal vasculature of pachychoroid eyes, especially based on en face OCT images. 1,4,6,[28][29][30] Ng et al 6 revealed that different exudative maculopathies show distinctive choroidal vasculature morphology and can be classified accordingly. Vascular density had a greater diffuse pattern of dilated vessels in pachychoroid eyes compared to nonpachychoroid AMD eyes in quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular density had a greater diffuse pattern of dilated vessels in pachychoroid eyes compared to nonpachychoroid AMD eyes in quantitative analysis. 4,30 These morphologic differences can serve as features that could distinguish pachychoroid from nonpachychoroid eyes for DCNNs.…”
Section: Discussionmentioning
confidence: 99%